Non-Financial KPIs: The Relationship Between BUMDes Personnel Performance and Financial KPIs - Subaeti Subaeti; Kamaludin Kamaludin; Fachruzzaman Fachruzzaman; Husaini Husaini (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to examine the influence of BUMDes personnel performance on financial KPIs, with non-financial KPIs serving as a mediator. The sample for this research consists of BUMDes in Bengkulu Province, with a total of 60 observations. The data used is primary data collected through questionnaires. The independent variable is BUMDes personnel performance, which is measured using four indicators: work quality, quantity of work, timeliness of work, and work effectiveness. The mediating variable is the non-financial KPI, measured by three indicators: customer satisfaction metrics, the ratio of repeat customers to new customers, and market share. The dependent variable in this research is the financial KPI, which is measured using three indicators: Gross Profit Margin, Net Profit Margin, and Current Assets. The results prove that: (1) BUMDes personnel performance has a positive and significant effect on financial KPIs; (2) BUMDes personnel performance has a positive and significant effect on non-financial KPIs; (3) financial KPIs have a positive and significant effect on financial KPIs; and (4) non-financial KPIs fully mediate the influence of BUMDes personnel performance on financial KPIs. The findings of this research strengthen stewardship theory and the balanced scorecard approach. Therefore, it is hoped that the follow-up to the results of this research will provide important insights for BUMDes managers in Bengkulu Province in designing strategies to improve organizational performance.